Penerapan model pembelajaran take and give terhadap kemampuan komunikasi matematis siswa - Sri Yunita Ningsih; Helma Mustika; Ramadhani Fitri; Puji Astuti; Yunisa Fadhilah Hartati; Della Armilasari Dalimunthe (Mahesa Research Center, 2022)
This study aims to determine differences in mathematical communication abilities between students in classes receiving take-and-give learning and students in classes receiving conventional learning. This research is experimental, with a quasi-experimental research design with a nonequivalent control group research design. The data collection technique used a five-problem student mathematical communication test, and the data analysis included prerequisite tests (normality test and homogeneity test), while the hypothesis test used a two-mean comparison test (t test). The results of the tests that have been carried out show that the calculated t value is greater than the t table value. Thus, it can be concluded that students' mathematical communication abilities with the application of the take and give learning model are better than their mathematical communication abilities with conventional learning on triangle material in grade 7.